Blood meal digestion and changes in lipid reserves are associated with the post-ecdysis development of the flight muscle and ovary in young adults of Rhodnius prolixus. (April 2023) - Braz, Valdir; Selim, Lukas; Gomes, Geyse; Costa, Manoel Luis; Mermelstein, Claudia; Gondim, Katia C.
Graphical abstract: Highlights: In adults of Rhodnius prolixus, the midgut is still full of blood after the ecdysis. Lipid and protein contents of the fat body decrease in the days after molting. The flight muscle develops after the ecdysis. The muscle fiber accumulates lipids and increases in size. Abstract: Rhodnius prolixus is a hemimetabolous, hematophagous insect, and both nymphs and adults feed exclusively on blood. The blood feeding triggers the molting process and, after five nymphal instar stages, the insect reaches the winged adult form. After the final ecdysis, the young adult still has a lot of blood in the midgut and, thus, we have investigated the changes in protein and lipid contents that are observed in the insect organs as digestion continues after molting. Total midgut protein content decreased during the days after the ecdysis, and digestion was finished fifteen days later. Simultaneously, proteins and triacylglycerols present in the fat body were mobilized, and their contents decreased, whereas they increased in both the ovary and the flight muscle. In order to evaluate the activity of de novo lipogenesis of each organ, the fat body, ovary and flight muscle were incubated in the presence of radiolabeled acetate, and the fat body showed the highest efficiency rate (around 47%) to convert the taken up acetate into lipids. The levels of de novo lipid synthesis in the flight muscle and ovary were very low. When 3 H-palmitate was injected into the young females, its incorporation by the flight muscle was higher than by the ovary or the fat body. In the flight muscle, the 3 H-palmitate was similarly distributed amongst triacylglycerols, phospholipids, diacylglycerols and free fatty acids, while in the ovary and fat body it was mostly found in triacylglycerols and phospholipids. The flight muscle was not fully developed after the molt, and at day two no lipid droplets were observed. At day five, very small lipid droplets were present, and they increased in size up to day fifteen. The diameter of the muscle fibers also increased from day two to fifteen, as well as the internuclear distance, indicating that muscle hypertrophy occurred along these days. The lipid droplets from the fat body showed a different pattern, and their diameter decreased after day two, but started to increase again at day ten. The data presented herein describes the development of the flight muscle after the final ecdysis, and modifications that occur regarding lipid stores. We show that, after molting, substrates that are present in the midgut and fat body are mobilized and directed to the ovary and flight muscle, for the adults of R . prolixus to be ready to feed and reproduce.